NILAI MORAL DALAM NOVEL MENARI DI ATAS AWAN KARYA MARIA A. SARDJONO TINJAUAN SOSIOLOGI SASTRA - Khusnul Hatimah; Totok Priyadi; Agus Wartiningsih (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis reseach was motivated by the researcher's interest to find moral values of novel, work of Maria a. Sardjono, entitled. Menari di Atas Awan. The set of problems in this research were what kind of moral values that can reflected in this novel and the learning process of Bahasa Indonesia in SMA,/MA level. The purpose of this research was to describe those problems. The theories used in this research were: moral value, kinds of moral value, novel, the sociologist literatue, the learning of literature in the school, and the plan of learning implementation.The method used was descriptive with the form of qualitative. The approach used in this research was Literature socoilogist. The technique of analysing the data was content analysis. The result of this research about the moralvalue were:(1) divinity; praying to the almighty god.; (2) Humanity; responsibility, loving, and respectful; (3) Ownself; Honesty, and hard-working; also (4) the implementation of moral value in the novel as a learning tool of bahasa in the aspect of curriculum, the purpose, the choosing of learning instrument and worthiness to be used as an instrument for learning bahasa for XII students level. The result of this research were expected to be used by the teacher and could be used as an instrument of learning in the school and also the researcher expected that this resultcould be able to provide suggestion for the future conductor of this novel. Keywords: Moral Value, Novel, Sociology Sastra